2014
DOI: 10.2147/dddt.s66981
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of gentamicin dosing nomograms

Abstract: BackgroundSeveral nomograms have been proposed to facilitate the determination of initial gentamicin dosing regimens in clinical settings. This study aimed to assess the predictive performance of these nomograms in Korean patients.MethodsGentamicin concentrations were determined in 84 patients with infective endocarditis (IE) and in 95 patients with other infections. All patients underwent therapeutic drug monitoring in Seoul National University Hospital from 2006 to 2012. Individual pharmacokinetic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the case of Gram-positive and most Gram-negative infections other than UTIs, AGs are usually administered in combination with cell wall-targeting agents such as beta-lactam antibiotics or vancomycin rather than as a monotherapy. They are used synergistically to treat endovascular infections caused by Enterococcus spp., Staphylococcus aureus, Streptococcus spp., and Listeria [14,30,[66][67][68][69][70][71][72][73][74][75][76]. An overview of the dosing regimens of AGs for patients with abnormal kidney functions is provided in Tables 3-5.…”
Section: Current Dosing Schemes For Patients With Abnormal Kidney Fun...mentioning
confidence: 99%
“…In the case of Gram-positive and most Gram-negative infections other than UTIs, AGs are usually administered in combination with cell wall-targeting agents such as beta-lactam antibiotics or vancomycin rather than as a monotherapy. They are used synergistically to treat endovascular infections caused by Enterococcus spp., Staphylococcus aureus, Streptococcus spp., and Listeria [14,30,[66][67][68][69][70][71][72][73][74][75][76]. An overview of the dosing regimens of AGs for patients with abnormal kidney functions is provided in Tables 3-5.…”
Section: Current Dosing Schemes For Patients With Abnormal Kidney Fun...mentioning
confidence: 99%
“…The main areas of inappropriate practices were inappropriate sampling times and inappropriate post-analytical actions including inappropriate dose adjustments. Globally, challenges related to gentamicin optimal dosing, monitoring and TDM application in clinical settings continue to be published in the recent literature (Al-Lanqawi et al, 2007 ; Crcek et al, 2019 ; Hartman et al, 2020 ; Kadambari et al, 2011 ; Lee et al, 2014 ; Valitalo et al, 2015 ). Compelling evidence has proven that gentamicin dosing nomograms performed poorly in achieving therapeutic gentamicin pharmacokinetic targets and emphasise the crucial need for appropriate TDM to guide gentamicin dosing in various populations (Al-Lanqawi et al, 2007 ; Lee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, challenges related to gentamicin optimal dosing, monitoring and TDM application in clinical settings continue to be published in the recent literature (Al-Lanqawi et al, 2007 ; Crcek et al, 2019 ; Hartman et al, 2020 ; Kadambari et al, 2011 ; Lee et al, 2014 ; Valitalo et al, 2015 ). Compelling evidence has proven that gentamicin dosing nomograms performed poorly in achieving therapeutic gentamicin pharmacokinetic targets and emphasise the crucial need for appropriate TDM to guide gentamicin dosing in various populations (Al-Lanqawi et al, 2007 ; Lee et al, 2014 ). For example, a recent systematic review reported decreased target attainment with gentamicin in critically ill children (Hartman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 20 Also, for empirical therapy (<48 hours) monitoring of plasma concentrations is not required. 21 Although the Australian therapeutics guidelines (2016) 22 recommend the use of a computerized method with a dosage adjustment to achieve a target AUC, they also realize that not all hospitals would have access to these computer programs. Hence, nomograms were included and the nomograms continue to be used by some units in NSW.…”
Section: Discussionmentioning
confidence: 99%